Frequência e repercussão da sobrecarga de cuidadoras familiares de idosos com demência - Claudia Fernandes da Silva (2011)
This dissertation, consisting of an article, addresses the burden of family caregivers of dementia patients, the task of caring, the caregivers role, how the choice of the caregiver is determined, what functions they exercise, and the consequences of this burden in their physical, mental and emotional health. The Alzheimers disease, followed by vascular dementia, is the main cause of irreversible dementia, especially in elders over the age of 65. The growth of the elder population and the increase of life expectancy are accompanied by the increase of the demand of uninformed family caregivers. That generates much demand and many activities to the caregivers and a consequent burden, due to their physical and mental efforts, which can lead to anxiety and depression. In this cross-sectional and analytical study, performed in a convenience sample of 58 family caregivers who participated in support groups for families of people with dementia, to investigate the prevalence and factors associated to burden, common mental distress and self-perception of memory.In the final model the following characteristics predominated: association of burden with occupation (p=0,014), sports (p=0,010), religion (p=0,032) and time exercising the caregiver activities (p=0,046). Related to the minor mental disorders the relevant associations were sports (p=0,028), back pain (p=0,026) and daily care time (p=0,037). Memory complaints were statistically associated to the use of antidepressants (p=0,034). Despite having characteristics that could contribute to a smaller burden and participating in a support group, the caregivers still showed a mild to moderate burden